MonedaPAR: an argentine alternative for the social and solidarity economy - Candelaria Pardo, Eugenia (REVESCO. Revista de Estudios Cooperativos, 2020)
MonedaPAR is an Argentine digital currency created in 2017 complementary to the legal tender. Being founded on the technology that provides blockchain is inserted within the global technological changes, the debate on the speculation that touches the cryptocurrencies and the history of social currencies in Argentina. It is developed in turn in a recessive context economy, with the desire to be an alternative for the social and solidarity economy, small and medium companies, recovered companies and consumers; whenever the increase in the prices of food, transport or rates leads to the dispensing of goods and services, producers will be left without buyers and vice versa. Thus, truly yearns to sponsor the transactions of goods, services and knowledge based on values such as responsibility, mutual aid and solidarity. The article proposes a reading of the global context, marked by an unsolved financial crisis of capitalism, social inequalities and technological changes; but also, it offers an overview of national economic measures and its impact on social and solidary economy organizations. Then is presented the dilemma raised by the cryptocurrencies, in addition to the objectives, strengths, weaknesses, threats and opportunities that MonedaPAR poses. It will be done with a descriptive-interpretative look considering researches carried out and in course at the Institute of Latin American Integration -IIL- of the National University of La Plata -UNLP; as well as interviews with key references linked to the creation, development and dissemination of MonedaPAR. It will make it possible to reflect on the functions of the currency and the policies and instruments necessary to promote greater equality; so that the world is for all and not for a few, and human life can be dignified in its broadest sense.